The Implementation of the Policy of Payment Using QRIS on Public Satisfaction in Medan City at Trans Metro Deli - Leli, Nur; Siregar, Saparuddin; Lubis, Fauzi Arif (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Implementation of the Indonesian Quick Response Code (QRIS) is important because the QRIS system is expected to increase ease of service. Transaction and have a positive impact on public interest and participation in using Tans Metro Deli public transportation. This research method is a quantitative method using SPSS 26, a data analysis tool in this research namely multiple linear regression. This research aims to prove that the payment variable has an effect on the satisfaction variable. This research uses a survey method obtained from the original scene of the incident by distributing questionnaires. A questionnaire is a data collection technique carried out by providing written questions submitted to respondents. the likert scale is used to measure the attitudes, opinions, or perceptions of a person or group of people about social phenomena with a likert scale, then the variables to be measured are described into variable indicators. The date sources used are primary and secondary sources. The number of respondents in this research was 30 people using a simple linear regression analysis technique. The analysis tool that the researcher used was SPSS software version 26 The research results show that payment has a significant positive effect on satisfaction. data analysis techniques used in this study descriptive statistical analysis, validity test and reliability test, classical assumption test there are several classical assumption tests used in this study are normality test, multicollinearity test and heteroscedasticity test, then simple linear regression analysis test, hypothesis test namely t test, f test and determination coefficient test. So the use of QRIS contributes significantly to increasing satisfaction in the city of Medan.